Analisis Perawatan Mesin Uji Tarik Kapasitas 50 Ton dengan Metode Reliability Centered Maintenance (RCM) pada PT. BK - Fernanda, Alif; Darajatun, Rizki Achmad (Fakultas Teknik Universitas Tulang Bawang, 2024)
This study applie the reliability Centered Maintenance (RCM) method to analyze the maintenance of tensile tensile testing machines at PT. BK. By collecting data on machine failures and reliability, the study conducts an analysis of failure causes and identifies critical failure mode. Based on the analysis, maintenance action are determined, including preventive maintenance, condition-based repairs, and the-based repairs. The effectiveness of these maintenance action is evaluated considering factors such as cost, time and impact on machine performance. The results of this study provide valuable insight fot planning optimal maintenance strategies of tensile testing machines, aiming to improve operational reliability, reduce downtime, and optimize maintenance cost. Keywords: Downtime, Reliability Centered Maintenance, Tensile Tasting Machines